Fabrication and characterization of mesopores in a silica gel matrix. (7th June 2018) - Cadena, Maria J.; Parker, John C.; Raman, Arvind; Reifenberger, Ronald G.
Abstract: The sol–gel synthesis of a silica (SiO2 ) matrix that surrounds ZnO nanoparticles was studied using atomic force microscope (AFM) techniques prior to and just after removal of the nanoparticles. The open silica matrix allows acids to penetrate and cause dissolution and removal of the ZnO nanoparticles. The nanoparticles serve as nanotemplates that allow the formation of cavities (mesopores) inside the silica matrix with comparable shape and size of the nanoparticles. AFM topographic scans revealed the presence of dome-like structures at the surface of the acid-treated silica matrix. Electrostatic force images of these near-surface, dome-like features revealed they have a low dielectric constant relative to the silica matrix, suggesting they are domes over empty cavities. Taken together, these results are consistent with the formation of a novel material consisting of nanotemplated cavities having a volume of ~0.1 attolitres embedded in a silica matrix.